2020
DOI: 10.7759/cureus.6667
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Gangrene as the Initial Presentation of Systemic Lupus Erythematosus in Emergency Department

Abstract: Systemic lupus erythematosus (SLE) is a chronic multisystemic autoimmune disease. Among the cutaneous manifestations of SLE, digital gangrene is considered to be very rare. This complication, which may lead to severe ischemic necrosis and amputation, is suggested to be the result of poor perfusion that is usually caused by vasculitis, vasospasm, thromboembolism, or atherosclerosis. Digital gangrene is seen mostly at a late stage of the disease proposing that a long history of SLE is a considered risk factor. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Although 8 of our patients were diagnosed with SLE while an adolescent [age 12-20 years], long duration of lupus (>/ = 4 years) is a known risk factor for the development of gangrene. 6,9 With a mean duration of SLE before the onset of the gangrene of 18.5 SD = 11.5 years, the development of gangrene in our cohort was consistent with previous reported studies, with most patients having the first episode of gangrene at a late stage of the disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although 8 of our patients were diagnosed with SLE while an adolescent [age 12-20 years], long duration of lupus (>/ = 4 years) is a known risk factor for the development of gangrene. 6,9 With a mean duration of SLE before the onset of the gangrene of 18.5 SD = 11.5 years, the development of gangrene in our cohort was consistent with previous reported studies, with most patients having the first episode of gangrene at a late stage of the disease.…”
Section: Discussionsupporting
confidence: 90%
“…Peripheral digital gangrene is a rare manifestation of SLE, being particularly unusual as a first presentation of the disease. 3,6,9 Although there are no recent reports about the prevalence in SLE patients, three previous studies reported a prevalence of gangrene in SLE patients between 0.6% and 5.8%. 1,6,10 In our cohort the prevalence was about 1%.…”
Section: Discussionmentioning
confidence: 99%
“…However, 3 of our patients concurrently received immunosuppressive agents in the form of cyclophosphamide or mycophenolate mofetil for their systemic manifestations. This was in stark contrast to all previous reports, wherein the protocol was to initiate cyclophosphamide along with steroids as first line agent [4,11,13]. Other agents of choice in previous reports included rituximab and IV prostanoids in refractory cases [1,12].…”
Section: Discussionmentioning
confidence: 74%
“…The actual prevalence of digital gangrene in MCTD remains unknown. Therefore, as new data is emerging from the developing world, it appears that the clinical characteristics and distribution of digital gangrene are different from western cohorts with MCTD and SLE being the commonly associated disorders rather than systemic sclerosis [10][11][12]. A cohort of lupus patients from India estimated the prevalence of digital gangrene in SLE as 5% [13] notably higher than previous data ranging from 0.6 to 1.2% suggesting that digital gangrene maybe commoner in South Asian region.…”
Section: Discussionmentioning
confidence: 92%
“…8 However, some cases of digital gangrene as a primary event in SLE have been reported. 3,6,[9][10][11] The majority of cases reported in the literature have proved that digital gangrene occurs in young SLE patients and that the occurrence of this complication in older adult patients is extremely rare. 2,6,9,10 To the best of the authors' knowledge, only three cases of digital gangrene have been reported in patients with SLE at an older age (after 50 years old).…”
Section: Discussionmentioning
confidence: 99%